Gaceta Técnica journal enters the Scielo repository (Gaceta Técnica, 2023)
The scientific journal Gaceta Técnica, considering the recommendations of the different evaluating entities, has been improving the publication process in order to optimize editorial quality, thus reaching a place in the SciELO Multidisciplinary Repository in 2022, which allows the preservation and dissemination of articles approved for publication in Gaceta Técnica on a larger scale
Keywords: Gaceta Técnica journal; SciELO; Universidad Centroccidental Lisandro Alvarado